2D Colloidal Array of Glucose‐Conjugative Conductive Microparticles for a Pressure‐Mediated Chemiresistive Sensor Platform. (6th July 2020) - Choi, Song‐Ee; Park, Daehwan; Hwang, Hyejin; Seo, Minjeong; Lee, Duho; Jeong, Unyong; Kim, Jin Woong
Abstract: A platform is introduced for pressure‐mediated chemiresistive glucose sensing based on a 2D array of glucose‐conjugating silver nanowire (AgNW)‐deposited conductive microparticles (AgCMPs). Glucose‐conjugating AgCMPs, as transducers of the sensors, are fabricated by decorating the surface of monodisperse polyurethane elastomeric MPs with AgNWs by layer‐by‐layer deposition. Then, the AgNWs are covalently bonded to 4‐mercaptophenylboronic acid (4‐MPBA) to endow them with chemiresistive glucose sensing property against the applied pressure. The 4‐MPBA‐functionalized AgCMPs are positioned with high accuracy on a hole‐patterned stencil film placed between electrodes. Using this sensor system, it is shown that the current induced by the application of constant pressure to the sensor film at a given supply voltage varies linearly with the glucose concentration before and after critical glucose bridging concentration. Notably, the AgCMP‐based chemiresistive sensors could detect glucose over a wide concentration range from 0.56 × 10 −6 m to 56 × 10 −3 m with remarkable sensitivity and selectivity. Abstract : A 2D colloidal array strategy of glucose‐conjugative conductive microparticles is proposed to fabricate a new type of chemiresistive glucose sensor. It is shown that such a glucose sensor is able to detect a wide range of glucose concentrations with high sensitivity, thus allowing the development of a noninvasive glucose sensor platform.